Penerapan Framework Laravel pada Sistem Informasi Arsip Dosen Fakultas Keguruan dan Ilmu Pendidikan - Aldom Restaldo; Yos Richard Beeh (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Information technology is essential for educational institutions, especially at the university level. In addition to helping in doing work, technology can save time in entering data that is still using the manual method. At the Satya Wacana Christian University Faculty of Teacher Training and Education, lecturer archives still use a manual and less structured system. This research uses a case study research form. The research method uses Research and Development by creating applications and testing the effectiveness of the method. Data collection techniques used are observation, interviews, and internet access. This research implements Laravel Framework. The design results produce an online-based SIPA application that can facilitate information, coordination, and well-structured lecturer storage archives.